Safety and efficacy of Sacox(®) microGranulate (salinomycin sodium) for chickens for fattening and chickens reared for laying - Rychen, Guido (EFSA J, 2017)
Salinomycin sodium (SAL‐Na) is active against certain Gram‐positive bacteria, while Gram‐negative species are resistant. SAL‐Na at the proposed concentration is unlikely to increase shedding of Salmonella, Escherichia coli and Campylobacter and or induce resistance and cross‐resistance to antimicrobials important in human and animal therapy. SAL‐Na is safe for chickens for fattening at 70 mg/kg complete feed, for chickens reared for laying at 50 mg/kg complete feed in the first 12 weeks of life. The simultaneous use of SAL‐Na and certain antibiotic drugs (e.g. tiamulin) is contraindicated. SAL‐Na is absorbed and extensively metabolised. Metabolites have reduced ionophoric activity. SAL is the marker residue (MR). No residues in eggs are expected. SAL‐Na is not genotoxic and not a carcinogen. A NOAEL of 0.5 mg/kg body weight (bw) per day is derived from a cardiovascular study in dogs as well as from a 12‐month dog study. Consumer exposure complies with an acceptable daily intake of 0.005 mg SAL/kg bw after 1 h withdrawal. A withdrawal time and maximum residue limits are not considered necessary. SAL‐Na from Sacox(®) is not an irritant to skin and eyes; it is a potential sensitiser to skin and the respiratory tract. A toxicological risk by inhalation for persons handling the additive cannot be excluded. SAL‐Na in feed for chickens will not pose a risk for the aquatic environment. A risk for the terrestrial ecosystem is considered unlikely due to metabolisation and the rapid degradation of SAL in the environment. SAL‐Na at a minimum concentration of 50 mg/kg complete feed is an effective coccidiostat for chickens for fattening. This conclusion is extended to chickens reared for laying. SAL‐Na in Sacox(®) 120 microGranulate and Sacox(®) 200 microGranulate is considered bioequivalent with respect to its anticoccidial effect.